Odpowiedzi

2009-11-07T20:40:47+01:00
(2x)²:4=4x²:4=x²
(4x²y³)ˉ²=(1/4x²y³)²=1/(16x⁴y⁶)
(baca)²:(baba)²=b²a²c²a²:b²a²b²a²=a⁸b²c²
do²·(zoo)ˉ³=do²·(1/zoo)³=do²·1/z³o³o³=do²/z³o⁶=d/z³o⁴
2009-11-07T21:21:21+01:00
(2x)²:4=4x²:4=x²
(4x²y³)ˉ²=(1/4x²y³)²=1/(16x⁴y⁶)
(baca)²:(baba)²=(b²a²c²a²):(b²a²b²a²)=(a⁴b²c²):(a⁴b⁴)=b⁻²c²
do²·(zoo)ˉ³=do²·(1/zoo)³=do²·1/z³o³o³=do²/z³o⁶=d/z³o⁴
2009-11-07T21:30:06+01:00
(2x)²:4=x²
(4x²y³)ˉ²= (1/4x²y³)² = 1/8x⁴y⁶
(baca)²:(baba)²=(b²a²c²a²):(b²a²b²a²)= (b²a⁴c²): (b⁴a⁴) = a8b⁶c²
do²·(zoo)ˉ³=do²·(1/zoo)³=do²·1/z³o³o³=do²/z³o⁶=d/z³o⁴